PENERAPAN PRINSIP EKOWISATA DALAM PENGEMBANGAN DESTINASI PARIWISATA BERKELANJUTAN PADA TAMAN HUTAN RAYA PAKAL SURABAYA - Michelle, Kathleen; Agoes Tinus Lis Indrianto (Jurnal Sains Terapan Pariwisata, 2025)
Purpose: The development of the tourism sector plays a crucial role in economic progress, both in developing and developed countries. Ecotourism emerges as an alternative form of tourism that focuses on environmental, social, and economic sustainability and has significant potential in providing economic benefits to local communities and environmental conservation. This study aims to identify the ecotourism potential and strategies for its implementation in the sustainable tourism development of Taman Hutan Raya Pakal Surabaya. Research Methods: Using a qualitative approach, data was obtained through direct observation, in-depth interviews with various stakeholders, and literature review. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Implication: The results of the study indicate that ecotourism in Taman Hutan Raya Pakal Surabaya has great potential that has not yet been fully explored. The development of ecotourism involving active participation of the local community can have a positive impact on their well-being and environmental conservation. These findings are expected to serve as a foundation for the development of ecotourism in other destinations and to make a tangible contribution to sustainable tourism development in Indonesia.